Impact of electricity shortages during energy transitions in Taiwan. (15th May 2018) - Wu, Kuei-Yen; Huang, Yun-Hsun; Wu, Jung-Hua
Abstract: Taiwan has been limited by several factors in its pursuit of energy transitions and rapid development of green energy, including goals of achieving a nuclear-free homeland, reducing air pollution, and restrictions on receiving capacity of liquefied natural gas reception terminals. In other words, Taiwan is restricted to use nuclear energy or thermal power generation as transitional technologies to bridge the gap in electricity supply-demand before the maturation of renewable energy technologies. If electricity demand continues to grow, Taiwan will face the risk of electricity shortages, which will affect industrial sectors. This study applied the supply-driven input-output and the price models to analyse economic impacts of electricity shortages on each sector. The simulation results revealed that when electricity supply was reduced by 1 kWh, Taiwan's overall economic output would decrease by 8.98 NTD in 2011. A comparison of these sectors shows that sectors with higher electricity allocation coefficients had higher direct output impacts, while those with higher forward linkages generated higher indirect output impacts. The findings also showed that in the majority of sectors, indirect output impacts were higher than direct output impacts. In other words, neglecting indirect output impacts will result in underestimation of total impacts of electricity shortages. Highlights: We analyse impact of electricity shortages during energy transitions in Taiwan. Direct and indirect output impacts are analysed by using the supply-driven I-O model. The test of the joint stability of I-O coefficients is conducted prior to the analysis. Indirect output impacts are higher than direct output impacts in the majority of sectors. Price impacts are affected by electricity input coefficients.